2019
DOI: 10.1016/j.rmcr.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic tuberculous empyema by intrapleural injection of anhydrous ethanol

Abstract: BackgroundAnhydrous ethanol, for its part, has been successfully used to treat renal cyst, hepatocellular carcinoma and ovarian chocolate cyst et al. However, in spite of the high frequency of tuberculous purulent pleural effusion, we found that only a few very early studies that attempted to assess the use of intrapleural anhydrous ethanol in tuberculous effusions with signs of empyema. We report a patient who was injected anhydrous ethanol into pleural cavity to treat chronic tuberculous empyema.Case present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…6,7 A similar study conducted by Nie et al showed intrapleural injection of anhydrous ethanol could achieve the purpose of eliminating the pus cavity, which is particularly suitable for patients who cannot tolerate surgery or are unwilling to undergo surgical treatment. 8 A study conducted by Raza et al concluded that operating patients early with T.B empyema thoracis carries similar results if compared to those operated at a later stage. 9 A study conducted by Jen et al, the treatment outcome of tuberculous empyema is less satisfactory than that of pulmonary tuberculosis, however, modem multidrug chemotherapy with repeated drainage and opportune surgical interventions could be in prospect of successful treatment of tuberculous empyema.…”
Section: Discussionmentioning
confidence: 96%
“…6,7 A similar study conducted by Nie et al showed intrapleural injection of anhydrous ethanol could achieve the purpose of eliminating the pus cavity, which is particularly suitable for patients who cannot tolerate surgery or are unwilling to undergo surgical treatment. 8 A study conducted by Raza et al concluded that operating patients early with T.B empyema thoracis carries similar results if compared to those operated at a later stage. 9 A study conducted by Jen et al, the treatment outcome of tuberculous empyema is less satisfactory than that of pulmonary tuberculosis, however, modem multidrug chemotherapy with repeated drainage and opportune surgical interventions could be in prospect of successful treatment of tuberculous empyema.…”
Section: Discussionmentioning
confidence: 96%